An exponential smoothing method application to restoring lost data on electric power technical record-keeping in industrial enterprises - Ya.S. Bederak (National Technical University "Kharkiv Polytechnic Institute", 2014)
The paper studies in detail a problem of restoring single data of electric power technical record-keeping systems by means of exponential smoothing. A hypothesis of efficient finding the optimal value of smoothing constant α in the range of 0 < α < 2 is tested. Variation ranges for the mean absolute percentage error of the forecast are specified versus values of the time series variation coefficient for specific electricity consumption processes with different data spread.